Bovine lactoferrin purification from whey using Yellow HE-4R as the chromatographic affinity ligand - Baieli, María Fernanda (2014)
The worldwide production of whey increases by around 186 million tons each year and it is generally considered as a waste, even when several whey proteins have important economic relevance. For its valorization, inexpensive ligands and integrated chromatography methods need to be developed for specific and low-cost protein purification. Here, we describe a novel affinity process with the dye Yellow HE-4R immobilized on Sepharose for bovine lactoferrin purification. This approach based on a low-cost ligand showed an efficient performance for the recovery and purification of bovine lactoferrin directly from whey, with a yield of 71% and a purification factor of 61.